ANALISIS FAKTOR YANG MEMPENGARUHI PENDAPATAN INDUSTRI KECIL MENENGAH DI KOTA DUMAI - Febriandi Rahmad i; Isyandi Isyandi; Pailis Armas Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine how much influence the capital, the number of hours worked and the length of business to business income. The object which is used as the target of this research is the small and medium industry in Dumai City. The sample used in this study were 74 small and medium industrial business units using proportional stratified random sampling method. Conducted in JuneJuly 2020. The method of analysis used in this research is quantitative descriptive method with data explanation in the form of numbers, using multiple linear regression analysis tools with the help of the SPSS version 23.0 application. Based on the results of the analysis, it shows that the variables of business capital and length of business have a positive and significant effect on the income of small industry enterpreneur. Meanwhile, the variable number of hours worked has a negative value and has no effect on the income of small industry enterpreneur. The variable that has the largest partial regression coefficient is the variable capital, with a coefficient value of 0.168 and a significant level of 0.000, this shows that the variable capital is the variable that has the most influence or dominance on the income of small industry enterpreneur at Dumai City.Keywords: capital, small and medium industry, number of hours worked, length of business, income